PERAN KEWIRAUSAHAAN DALAM MENDORONG PERTUMBUHAN PENDIDIKAN EKONOMI DI STIH PADANG - Nurhapani, Nurhapani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Entrepreneurship education has been taught as an independent scientific discipline, because entrepreneurship education at STIH Padang is explained as follows: 1. Entrepreneurship contains a complete and real body of knowledge, namely there are complete theories, concepts, and scientific methods. 2. Entrepreneurship has two concepts, namely start-up and venture-growth ventures, this is clearly not included in the general management education framework that separates management and business ownership. 3. Entrepreneurship is a discipline that has its own object, namely the ability to create something new and different. 4. Entrepreneurship is a tool for creating business equity and income distribution.